Aportes ecológicos para la biogeografía de la provincia de Mendoza - Roig, Virgilio Germán; Contreras, Julio Rafael (Ecosur, 2025)
All the available up to date Information about the herpetofauna and the avifauna of the Province of Mendoza was analyzed in the present paper. Data about the 56 species of amphibians and reptiles, and the 274 species of birds of Mendoza were used to construct three contour maps showing respectively the isogramic pattern of the herpetofauna, and the faunas of non-passerine and passerine birds. The species density contours were traced superposing a rectangular grid with quadrates of 100 kilometers each side to a map of the Province of Mendoza. The total number of species of the three considered taxa were expresed in each quadrate, and then the isograms were traced connecting the interpolated points with the same density valué at a defined interval. The basic patterns of the three isogramic maps are almost the same. The maps also show the gradual decline in the number of species westward from the great diversity of the east región (the Monte), and the presence of fronts of exceptionally rapid changes in species density at the foot of the Precordilleran mountains and on the east side of the plateau of Payunia, revealing the existence of geographical and ecological barriers separating the recognized previously Andean and Central faunistic areas. The derived pattern of biotic composition shows remarkable resemblance to the faunal subdivisions proposed by earlier workers who used non quantitative methods for the classification. In spite of having incomplete data, and the lack of more precise knowledge of systematics, ecology and geographical range of many considered species, this is the first quantitative approach to the biogeography of Mendoza Province.